Transactional Communication of Garut People in Dealing with Potential Natural Disaster - Damayanti Wardyaningrum; Setio Budi Hendro Hutomo (Komunikator, 2022)
Villages in West Java are some of the most hydrometeorology disaster-prone areas. Giri Awas in Garut is one of the villages in West Java whose area is located on the hills of mountain slopes. Some areas have undergone transfer from the forest into the plantation, which caused a higher risk of flood and landslides. This research aimed to identify how the communication is carried out by villagers to mitigate the risk of disaster. This research uses the concept of a transactional communication model with a descriptive qualitative method by collecting data through interviews and field observation. The researchers found the transactional communication model as the effort for disaster risk mitigation has been conducted by the village apparatus toward society. However, some aspects of transactional communication have not been optimally done. It has not been conducted continually, and messages related to disaster experiences in the past have not been communicated to the whole society. There are some unused potentials of the people to support the sustainability of transactional communication by utilizing local culture and other social groups. Optimizing society’s potential can support the negotiation of meaning between local government and society.